The influence of orientation on the behaviour of the acoustic emission in face centered cubic metal single crystals compressed in a channel-die - A. PAWEŁEK; A. PIĄTKOWSKI; Z. JASIEŃSKI; S. PILECKI (Archives of Acoustics, 2014)
The influence of the crystallographic orientation on the behaviour of the acoustic emission (AE) in face centered cubic (FCC) metal and alloy monocrystals compressed in channel-die is investigated using five differently oriented copper single crystals ({100} , {011} , {112} , {111} and {001} ). The results obtained are also compared to the AE behaviour in silver and to the low-temperature AE behaviour in copper and copper-aluminium alloy single crystals of identical {112} orientations. It has been stated that the orientation of crystal affects the final stage of the microstructure evolution (shear bands of the V or X shape or the bands of complex structure), and the orientation dependence of the AE behaviour is only a consequence of the orientation dependence of the deformation mechanisms. In general, however, the AE behaviour is strongly correlated with strain localization related to twinning and shear band formation, and is of universal character since it is similar in all the orientations applied. The observed correlations between the AE and the strain localization mechanisms are discussed on the basis of the dynamic and nonlinear (solitary wave) properties of dislocations. Consequently, it has been stated that the dynamics of shear band formation is markedly weeker than that in the case of twinning seems to indicate the crystallographic character of the shear band propagation since the non-crystallographic slip should be accompanied by strong acoustic effects.